Granulocyte-macrophage colony-stimulating factor-armed oncolytic measles virus is an effective therapeutic cancer vaccine - Großardt, Christian; Engeland, Christine Elisabeth; Bossow, Sascha; Halama, Niels; Plath, Karim; Leber, Mathias Felix; Springfeld, Christoph; Jäger, Dirk; Kalle, Christof von; Ungerechts, Guy (Human gene therapy, 2013)
Oncolytic measles viruses (MV) derived from the live attenuated vaccine strain have been engineered for increased antitumor activity, and are currently under investigation in clinical phase 1 trials. Approaches with other viral vectors have shown that insertion of immunomodulatory transgenes enhances the therapeutic potency. In this study, we engineered MV for expression of the cytokine granulocyte-macrophage colony-stimulating factor (GM-CSF). For the first time, therapeutic efficacy and adaptive immune response in the context of MV oncolysis could be evaluated in the previously established immunocompetent murine colon adenocarcinoma model MC38cea. MC38cea cells express the human carcinoembryonic antigen (CEA), allowing for infection with retargeted MV. Intratumoral application of MV-GMCSF significantly delayed tumor progression and prolonged median overall survival compared with control virus-treated mice. Importantly, more than one-third of mice treated with MV-GMCSF showed complete tumor remission and rejected successive tumor reengraftment, demonstrating robust long-term protection. An enhanced cell-mediated tumor-specific immune response could be detected by lactate dehydrogenase assay and interferon-γ enzyme-linked immunospot assay. Furthermore, MV-GMCSF treatment correlated with increased abundance of tumor-infiltrating CD3+ lymphocytes analyzed by quantitative microscopy of tumor sections. These findings underline the potential of oncolytic, GM-CSF-expressing MV as an effective therapeutic cancer vaccine actively recruiting adaptive immune responses for enhanced therapeutic impact and tumor elimination. Thus, the treatment benefit of this combined immunovirotherapy approach has direct implications for future clinical trials.